The Inherent Right of Indigenous Governance - McNeil, Kent (Osgoode Digital Commons, 2017)
I would like to start by acknowledging and thanking the Algonquin Nation, on whose unceded territory we are meeting. When the Dominion of Canada was created in 1867 by the UK Parliament, the BNA Act gave the Parliament of Canada exclusive jurisdiction over “Indians, and Lands reserved for the Indians”. Parliament used this authority to enact the Indian Act in 1876. That statute gave the Canadian government the power to impose the band council system on First Nations without their consent. The governance authority of First Nation band councils is therefore delegated authority – it comes from the Indian Act and applies only on reserves. Band councils as such have no jurisdiction over First Nations’ traditional territories beyond the boundaries of reserves.